2017
DOI: 10.1016/j.ajpath.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

CD14 Plays a Protective Role in Experimental Inflammatory Bowel Disease by Enhancing Intestinal Barrier Function

Abstract: Intestinal homeostasis disturbance through intestinal barrier disruption presumably plays a key role in inflammatory bowel disease (IBD) development. Genetic and candidate gene analyses in an Il10-deficient IBD mouse model system identified Cd14 as a potentially protective candidate gene. The role of Cd14 in colitis development was determined using dextran sulfate sodium (DSS)-induced acute and an Il10-deficiency-induced chronic model of intestinal inflammation. Intestinal permeability was investigated by fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 60 publications
(76 reference statements)
2
29
0
2
Order By: Relevance
“…Previously, we identified that TLR2 and CD14 are essential for CMP-induced classical macrophage (M1) activation of peritoneal macrophages (29). TLR2 KO and CD14 KO mice are known to develop more severe colitis than wild-type (WT) mice in response to DSS treatments, indicating that both TLR2 and CD14 play protective roles (41,42). Therefore, we used 3%, instead of 4%, DSS and explored whether these chitin-binding proteins were responsible for anti-inflammatory effects of LCBs using male mice deficient in TLR2 and male mice deficient in CD14.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we identified that TLR2 and CD14 are essential for CMP-induced classical macrophage (M1) activation of peritoneal macrophages (29). TLR2 KO and CD14 KO mice are known to develop more severe colitis than wild-type (WT) mice in response to DSS treatments, indicating that both TLR2 and CD14 play protective roles (41,42). Therefore, we used 3%, instead of 4%, DSS and explored whether these chitin-binding proteins were responsible for anti-inflammatory effects of LCBs using male mice deficient in TLR2 and male mice deficient in CD14.…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear why dietary LCBs worsened CD14 KO colitis. In this regard, Buchheister et al (42) demonstrated that the intestinal barrier function is not affected by CD14 deficiency but is reduced in CD14 KO colitis. Alternatively, Wang et al (43) demonstrated that increased inflammatory cytokines, including IFN-␥, induce intestinal epithelial barrier dysfunction by upregulating myosin light-chain kinase expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD14 is mainly expressed on the surfaces of monocytes, macrophages, neutrophils, and DCs with a protective function in a dextran sodium sulfate induced colitis model 196,197 . Lack of CD14 results in increased proinflammatory cytokine expression and decreased expression of TJs in an IBD mouse model 198 . The proportion of monocytes is increased in the blood in patients with Crohn's disease and the proportion of CD14 high macrophages are strongly infiltrated in inflamed intestinal mucosa 199 …”
Section: Tight Junction In Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…CD14 acts as a coreceptor of Toll-like receptor (TLR) 4 and is directly involved in the detection of lipopolysaccharide (LPS) and activation of NF-κB [10]. In previous studies, our group demonstrated that CD14 has a protective function on barrier integrity in a dextran sodium sulfate-(DSS-) induced acute colitis mouse model [11]. We also showed that in wild-type (WT) but not in Cd14 -/mice, monoassociation with Escherichia coli Nissle 1917 (EcN) leads to increased expression of tight junction (TJ) components, associated with protection against bacterial translocation [12].…”
Section: Introductionmentioning
confidence: 99%